A Beginner's Guide to Begonias: Classification and Diversity - Julian Ginori; Alfred Huo; Caroline R Warwick (EDIS)
Begonia is the fifth largest genus of flowering plants with over 1,800 species and hybrids. Begonias are known by their bright, full flowers and also their leaves, which vary to showcase patterns, designs or color. Begonias have a pan-tropical distribution, occupying the tropical regions of every continent except Australia. Begonias are commonly used in the landscape, although their heat tolerance makes them more desirable as a potted plant or houseplant in Florida. Begonias thrive best in partially-shaded areas, as they are sensitive to bright light and should be protected from the Florida summers in particular. Begonias grow in USDA Hardiness Zones 3 – 11, and are often used as hanging baskets, flowerpots, garden beds, and in the landscape (Gardening Solutions 2019). This EDIS publication is for Florida gardeners and horticulturalists hoping to learn more about the different classifications of begonias, as well as those interested in learning more about this potential landscape or houseplant. https://edis.ifas.ufl.edu/ep581